From geopolitical fault-line to frontline city: changing attitudes to memory politics in Kharkiv under the Russo-Ukrainian war - Gnatiuk, Oleksiy; Homanyuk, Mykola (Hungarian Geographical Bulletin, 2023)
The article investigates changing attitudes to memory politics in Ukrainian city of Kharkiv. In February 2022, with the outbreak of the full-scale Russo-Ukrainian war, this geopolitical fault-line city became a frontline city with significant potential outcomes for urban identity and local geopolitical preferences, including attitudes to the national memory politics. The research is based on the comparative analysis of the two surveys among residents of Kharkiv, conducted in spring-summer 2018 and in autumn 2022 – before and after the full-scale war. The results of the surveys are analysed by means of descriptive statistics and binary logistic regression. Additionally, two focus groups were held in order to receive additional justification when interpreting the results of the survey. The research shows that the attitudes to Ukrainian nation-centric memory narrative, including both decommunisation and decolonisation, have significantly improved. Nevertheless, public attitudes to the memory politics in the frontline city are highly reflexive in nature and deeply embedded in the context of the ongoing war. The geopolitical divide, which existed before the war, has largely transformed into a cultural one, namely heterogeneity of attitudes to the Russian cultural heritage in the city. This softened albeit still existing divide has, to some extent, materialised in physical space and runs between the ardent supporters of decommunisation and decolonisation that massively fled from the atrocities of the war and their opponents who at most choose (or were obliged) to stay in the front-line city. The study reveals that military conflicts may either activate hidden geopolitical divides in geopolitical fault-line cities or contribute to their transformation or even disappearance.